OPTIMASI DEGRADASI FORBOL ESTER PADA BUNGKIL BIJI JARAK PAGAR (Jatropha curcas L.) OLEH LIPASE KECAMBAH JARAK PAGAR ACETONE-DRIED DENGAN METODE RESPONSE SURFACE METHODOLOGY DAN KINETIKA DEGRADASINYA - , AVITA KUSUMA WARDHANI; , Dr. Ir. Chusnul Hidayat ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Jatropha curcas seed cake, a by-product from biodiesel production, has a potential to be exploited as an excellent protein source rich in essential amino acids for food or feed. Its utilization is limited by the presence of phorbol esters as the main toxic compound. Phorbol esters act like structural analogs of fatty acid esters, so its ester bonds can be hydrolyzed by lipase. The objective of this research was to obtain the optimum conditions of phorbol esters degradation on Jatropha curcas seed cake using acetone-dried lipase from germinated Jatropha curcas seeds, and to determine a model of its degradation kinetic. Response Surface Methodology (RSM) using three-factors-three-levels Box Behnken design was used for evaluating the effects of the phorbol esters degradation factors including reaction time (24-32 h), ratio of buffer/solid (40/6-60/6 mL/g), and ratio of enzyme/cake (20/5-40/5 U/g) on the percentage of phorbol esters degradation. The experimental data on phorbol esters degradation were subjected to multiple linear regression analysis using MINITAB 15 software. It was found that the optimal conditions of phorbol esters degradation were 29.33 h, 51.11/6 (mL/g), and 30.10/5 (U/g) for reaction time, ratio of buffer/solid, and ratio of enzyme/cake, respectively. The predicted degradation of phorbol esters was 98.96%. The verification experiment value (98.91%) was not significantly different with the prediction value, indicated that the optimization of phorbol esters degradation in Jatropha curcas seed cake using acetone-dried lipase from germinated Jatropha curcas L. seeds by RSM was successfully developed. The degradation kinetic of phorbol esters could be described by a first-order rate equation [ ]=[ ]. , and the half time was 9.39 h.